2018
DOI: 10.1103/physrevx.8.021002
|View full text |Cite
|
Sign up to set email alerts
|

Interface-Induced Zeeman-Protected Superconductivity in Ultrathin Crystalline Lead Films

Abstract: Two-dimensional (2D) superconducting systems are of great importance for exploring exotic quantum physics. The recent development of fabrication techniques has stimulated studies of high-quality singlecrystalline 2D superconductors, where intrinsic properties give rise to unprecedented physical phenomena. Here, we report the observation of Zeeman-type spin-orbit interaction protected superconductivity (Zeeman-protected superconductivity) in 4-monolayer (ML) to 6-ML crystalline Pb films grown on striped incomme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 29 publications
2
73
0
Order By: Relevance
“…Previous studies found that Rashba-type SOC in 2D noncentrosymmetric superconductors can create novel mixed singlet-triplet pairing and leads to a moderate enhancement of B c2 [12,13]. Very recently, a new kind of 2D noncentrosymmetric superconductivity, called Ising superconductivity, has been discovered in transition metal dichalcogenides (TMDs) [14][15][16][17][18][19][20]. In these materials, the SOC generates Zeeman-like spin splittings for electrons near the K and K valleys.…”
mentioning
confidence: 99%
“…Previous studies found that Rashba-type SOC in 2D noncentrosymmetric superconductors can create novel mixed singlet-triplet pairing and leads to a moderate enhancement of B c2 [12,13]. Very recently, a new kind of 2D noncentrosymmetric superconductivity, called Ising superconductivity, has been discovered in transition metal dichalcogenides (TMDs) [14][15][16][17][18][19][20]. In these materials, the SOC generates Zeeman-like spin splittings for electrons near the K and K valleys.…”
mentioning
confidence: 99%
“…The findings presented here are relevant for noncentrosymmetric superconductors, where the applied magnetic field has an orthogonal component to the effective SOC field. This applies to a large class of materials [20], which besides monolayer TMDs include interface superconductivity [21] and artificial heterostructures [22].…”
mentioning
confidence: 99%
“…with the coefficients defined as (T, B) = 0, which is found in Refs. [5,18,21]. We plot B c (T ) in Fig.…”
mentioning
confidence: 99%
“…[1,2] To achieve an efficient water oxidation, it is necessary to developa ni nexpensivec atalystt hat can operate under ambient conditions with low overpotential in numerousc ycles withouta ny loss of catalytic activity.V arious research groups across the globe have been workingo nt he experimental and theoreticald esigna nd synthesis of homogeneous as well as heterogeneous water-oxidation catalysts (WOCs). [1][2][3][4][5][6][7] Among these, ah eterogeneous electrocatalyst is of particulari nterest because it offers extra stability, and the relevant electrocatalytic method can directly be implemented into devices. [8][9][10][11][12] The known heterogeneous WOCs are metal oxides, including spinel oxides, monomeric, dimeric,a nd tetrameric molecular complexes, polyoxometalates (POMs) and POM-supported metal complexes,v arious nano-materials, electrodeposited metals from aqueous solutionso fm etal salts, amorphous metal-oxide thin-films, and metal-organic framework (MOF)-containing compounds.…”
Section: Introductionmentioning
confidence: 99%